2001
DOI: 10.1590/s0100-879x2001001100014
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow fibroblasts in patients with advanced lung cancer

Abstract: In a previous study we demonstrated that the incidence of fibroblast colony-forming units (CFU-F) was very low in bone marrow primary cultures from the majority of untreated advanced non-small lung cancer patients (LCP) compared to normal controls (NC). For this reason, we studied the ability of bone marrow stromal cells to achieve confluence in primary cultures and their proliferative capacity following four continuous subcultures in consecutive untreated LCP and NC. We also evaluated the production of interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Other examples can be found in studies performed by Chasseing et al . (), who showed that stromal cells derived from the bone marrow of untreated lung and breast cancer patients had a deficient colony‐forming ability and were insufficient to form confluent cell layers, although the patients did not receive prior irradiation or chemotherapy (Hofer et al ., ).…”
Section: Patient‐specific Datamentioning
confidence: 99%
“…Other examples can be found in studies performed by Chasseing et al . (), who showed that stromal cells derived from the bone marrow of untreated lung and breast cancer patients had a deficient colony‐forming ability and were insufficient to form confluent cell layers, although the patients did not receive prior irradiation or chemotherapy (Hofer et al ., ).…”
Section: Patient‐specific Datamentioning
confidence: 99%
“…Abnormalities in the function of CFU-F may be one of the possible mechanisms underlying metastatic processes [16][17][18][19]. In previous studies, we have found that BM from untreated advanced lung cancer patients (LCP) and breast cancer patients (BCP), without prior irradiation and chemotherapy treatments and without bone and BM metastases, had defective CFU-F as refl ected by their colony-forming effi ciency (CFE) reduction and their defi cient capacity to form confl uent layers of stromal cells [20][21][22][23]. We now hypothesize that CFU-F in LCP and BCP are under the regulation of a defective microenvironment.…”
Section: Fibroblast Colony-forming Units (Cfu-f) Assaymentioning
confidence: 99%